Optimizing company performance with a web-based office administration system at PT. Perkebunan Nusantara - Fitrio, Harsyatria (Implementasi Manajemen & Kewirausahaan, 2024)
In the era of globalization as it is today, the development of industry has entered the era of industrial revolution 4.0, meaning 4.0 itself is the industrial revolution has reached the 4th wave of the development of the previous industrial revolution. After the Covid 19 pandemic VUCA phenomenon (Volatility, Uncertainty, Complexity, Ambiguity) became a scourge for companies that are not ready in the face of business dynamics at this time [1], the industrial revolution 4.0 itself triggered the occurrence of Quantum Leap where almost all companies are forced to change business processes from initially information technology systems / manuals to be spurred to develop IOT (Internet Of Thing) [2].based information technology systems PT. Perkebunan Nusantara as one of the State-Owned Enterprises (SOEs) optimizing their Company Value Chain by developed information systems on web-based Office administration through the OA Application (Office Automation). The design of OA itself aims to make the company's performance in this case office administration more efficient, agile and flexible because it makes more easier to be accessed by all users of the application, made it easier to convey Information both top down in the form of company policy instructions and bottom up such as licensing process etc. This Information System design replaces the archive system and administration of the correspondence that is still done manually, as well as an effort in improving the Company's Competitive Advantages.